2005
DOI: 10.1007/11502760_28
|View full text |Cite
|
Sign up to set email alerts
|

A Side-Channel Analysis Resistant Description of the AES S-Box

Abstract: Abstract. So far, efficient algorithmic countermeasures to secure the AES algorithm against (first-order) differential side-channel attacks have been very expensive to implement. In this article, we introduce a new masking countermeasure which is not only secure against first-order sidechannel attacks, but which also leads to relatively small implementations compared to other masking schemes implemented in dedicated hardware. Our approach is based on shifting the computation of the finite field inversion in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
198
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 236 publications
(199 citation statements)
references
References 13 publications
1
198
0
Order By: Relevance
“…In the particular case of the AES algorithm, some S-Box implementations have been proved to be DPA-resistant [3,23]. Nevertheless, as they rely on the algebraic structure of the AES S-Box, they are not generic.…”
Section: Procedures 1 S-box Calculationmentioning
confidence: 99%
See 3 more Smart Citations
“…In the particular case of the AES algorithm, some S-Box implementations have been proved to be DPA-resistant [3,23]. Nevertheless, as they rely on the algebraic structure of the AES S-Box, they are not generic.…”
Section: Procedures 1 S-box Calculationmentioning
confidence: 99%
“…Rijmen's remark has been used in [24,23,32,30] to fix the flaw of TMM when accessing S-Box: the so-called Tower Field Methods perform the inversion in F 2 8 by using masked multiplications and masked inversions in F 2 4 or F 2 2 .…”
Section: ])mentioning
confidence: 99%
See 2 more Smart Citations
“…In the open literature, the masking technique is among the most popular suggested ways to protect an implementation against Differential Power Analysis [1,6,7,18]. However, several works have shown that such protected devices are still sensitive to higher-order attacks, originally described in [13].…”
Section: Introductionmentioning
confidence: 99%